Optimizing the Maintenance and Utilization of Educational Play Tools in Early Childhood Education (Study of the Depok, Tangerang, Bogor) - Suharsiwi Suharsiwi; Farihen Farihen; Rohimi Zamzam; Erna Budiarti; Rd. Heri Solehudin; Susilahati Susilahati; Herwina Herwina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to evaluate the maintenance and utilization of Educational Game Tools (EGT) in early childhood education institutions located in Depok, Tangerang, and Bogor, Indonesia. Employing a mixed-methods approach, we collected data from 67 early childhood education teachers across 30 institutions through questionnaires, in-depth interviews, observations, and documentation. The quantitative analysis revealed that the average maintenance score of EGT was 76%, categorizing it as "good." Qualitative insights highlighted key maintenance practices, including routine inspections and prompt repairs, which are essential for ensuring the safety and functionality of the equipment. The findings underscore the importance of effective maintenance strategies in enhancing the educational environment and supporting children's holistic development. Recommendations for improving training programs for educators and increasing government support for EGT procurement and maintenance are also discussed.